Increasing Synchrony of Annual River‐Flood Peaks and Growing Season in Europe. Issue 17 (13th September 2019) - Balke, Thorsten; Nilsson, Christer
Abstract: In a changing climate, time sensitive ecological interactions such as pollination and predation are vulnerable to temporal mismatch with direct consequences for ecosystem functioning. It is not known if synchrony and asynchrony of ecological and physical processes such as flood disturbance and plant phenology may similarly be affected by climate change. Here, by spatially merging temperature and flood peak data, we show for the first time that in Central and Eastern Europe, annual river flood peaks increasingly occur within the thermal growing season. This is due to the combined effect of earlier spring onsets and later flood peaks. Such increased physical‐phenological synchrony may especially impact river biogeomorphology and riparian floodplain ecosystem functioning through uprooting of seedlings and increased hydraulic roughness during major flood events. Plain Language Summary: Life history events of organisms, such as the spring emergence of certain plant species or the onset of migration of animals, are determined by seasonal weather patterns (for example spring temperatures). Where river flooding potentially disrupts the development and movement of plants and animals in the floodplain, the timing of both the organism's behavior and the flood events becomes crucial. Our study shows that the timing of the biologically active growing season has changed in relation to the timing of annual river flood peaks in Europe since the 1960s. In Central and Eastern Europe especially flood peaks are generally occurring later, and the yearly growing seasons start earlier in spring. This has currently unknown consequences for the river and floodplain ecosystems but is likely to change the way river hydrology, plants, and sediments interact. We encourage further studies to investigate the effects of altered seasonal synchrony between physical (e.g., flooding) and ecological landscape processes. Key Points: Annual river‐flood peaking increasingly occurs within the thermal growing season in Central and Eastern Europe since the 1960s Spring advance and flood‐peak delay both contribute to increasing synchrony of flood peaking and growing season We discuss the potential consequences of increased synchrony such as higher hydraulic roughness and disturbance to seedling establishment